FEATURES OF DESIGNING GEOINFORMATION SYSTEMS FOR APPLICATION IN THE MILITARY SPHERE - Бондаренко, Е.; Писаренко, Р.; Левінськова, Н. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article is devoted to questions of substantiation of methodological positions and design of features of multifunctional geoinformation systems (GIS) for their practical application in the military sphere. The system of scientific principles of development of such of GIS was formulated. Their content was disclosed. The main possibilities of integrating the principles and means of providing the multifunctionality that were defined by the functionality of the software were presented. Keywords: geoinformation systems, GIS design, principles of GIS development, means of providing multiservice GIS.